2014
DOI: 10.1016/j.nedt.2014.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Developing and piloting the multiple mini-interview in pre-registration student midwife selection in a UK setting

Abstract: Background: Published research has shown the multiple mini interview (MMI) to be a reliable assessment instrument in medical and nursing student selection internationally. Objectives: To develop, pilot and examine the reliability of MMIs in pre-registration student midwife selection in one Higher Education Institution a UK setting. Design and setting: BSc (Hons) Midwifery Studies students at a Higher Education Institution in the UK volunteered to participate in 'mock' MMI circuits during the first week of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…A recent systematic review of compassion in healthcare [5] identified compassion as a patient right [18], central to codes of ethics across healthcare professions [19][20][21], a practice competency that should be evaluated in selecting medical and nursing student admissions, [22,23], a standard of care that healthcare providers must be trained in and systems must measure and report [11,17,24] and a dimension of quality care that should be assessed on an ongoing basis [17,25]. Despite these efforts, there is persistent evidence that a lack of compassion is a key contributor to failures within healthcare systems [11,17,21,25,26] and that receiving compassionate healthcare remains an important but unmet patient need [8,10,11,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of compassion in healthcare [5] identified compassion as a patient right [18], central to codes of ethics across healthcare professions [19][20][21], a practice competency that should be evaluated in selecting medical and nursing student admissions, [22,23], a standard of care that healthcare providers must be trained in and systems must measure and report [11,17,24] and a dimension of quality care that should be assessed on an ongoing basis [17,25]. Despite these efforts, there is persistent evidence that a lack of compassion is a key contributor to failures within healthcare systems [11,17,21,25,26] and that receiving compassionate healthcare remains an important but unmet patient need [8,10,11,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…At the University of Surrey, Callwood and her colleagues, presented the case for using MMIs in the recruitment of nursing and midwifery students (Callwood et al 2012) before following up with piloting this method by carrying out 'mock' MMIs with existing midwifery students. This pilot addressed a requirement of their University's Admissions Board for the adoption of this method as a new recruitment procedure (Callwood et al 2014). Despite certain limitations of this pilot, such as the use of a selfselected sample of students who were already admitted to the course, the MMI recruitment process was described as 'uneventful', attracted positive feedback from both assessors and students and was officially adopted by that institution for the recruitment of midwifery students.…”
Section: Methods Of Student Selectionmentioning
confidence: 99%
“…Following successful pilots and evaluations of face validity the MMI has been adopted in at least two Higher Education Institutions (HEIs) in the UK for undergraduate nursing programmes (Callwood et al 2012, Perkins et al 2013, Callwood et al 2014. HEIs are ideally placed to work alongside clinical colleagues to develop stations that will suitably test candidates' attributes for nursing.…”
Section: Methods Of Student Selectionmentioning
confidence: 99%
See 2 more Smart Citations